Arabic Version of the Leahy Emotional Schemas Scale-II - Magda Ghassan Fathy; Khaled Jamal Mandoob (Iranian Journal of Psychiatry)
Objective: This study aimed to translate the Leahy Emotional Schemas Scale-II (LESS-II) into Arabic and validate its psychometric properties among Iraqi university students. The hypothesis was that the Arabic version would retain the original factor structure and demonstrate robustness and validity.